Evolution of sexually selected traits across animals - Tuschhoff, E.; Wiens, John J. (Frontiers in Ecology and Evolution, 2023)
Sexual selection is thought to be a major driver of phenotypic diversity and diversification in animals, but large-scale evolutionary patterns in sexually selected (SS) traits remain largely unknown. Here, we survey and analyze the evolution of these traits across animal phylogeny. We find that female mate choice appears to be the most widespread mechanism of sexual selection, but male-male competition appears to be almost as frequent in chordates and male mate choice is also common in arthropods. Among sensory types, tactile traits appear to be most widespread whereas auditory traits are relatively uncommon. Rather than being ubiquitous or randomly distributed across animals, most of these different types of SS traits are confined to clades in arthropods and chordates, which form “hotspots” for the evolution of these diverse trait types. Thus, different sensory types show accelerated rates of evolution in these clades. Moreover, different types of SS traits are strongly correlated with each other in their evolution across animals. Finally, despite the intensive interest in the role of sexual selection in speciation, we find only limited support for the idea that SS traits drive large-scale patterns of diversification and species richness across all animals.